Investigations on heat and mass transfer in gas diffusion layers of PEMFC with a gas–liquid-solid coupled model. (15th June 2022) - Jiao, Daokuan; Jiao, Kui; Zhong, Shenghui; Du, Qing
Graphical abstract: Highlights: A gas–liquid-solid coupled solver is implemented and validated in OpenFOAM platform. Accompanied heat conduction and convection during the water transport are crucial. Liquid water transport has minimal impact on the electrical conduction. Investigation on the vapor condensation and conjugate heat transfer with the coupled model. The coupled model can provide a realistic temperature distribution in compressed GDL. Abstract: Improvement of heat and water management in gas diffusion layers (GDL) is a critical issue to high-performance proton exchange membrane fuel cells (PEMFC). In this study, we develop a gas–liquid-solid coupled solver to simultaneously model the liquid water transport, vapor condensation, conjugate heat transfer, electric conduction and their interactions. A stochastic method is employed to reconstruct the 3D structural GDL. The compression effect on the geometry during assembly is included by applying a 10% compression deformation before converting to the solid fibrous zone in the simulation. The micro-porous layer (MPL) cracks are assumed to be the intake paths of the water transport. The impacts of the liquid water distribution on the heat transfer are investigated. For the whole heat transfer process, the heat conduction is the major approach through the solid fibrous layers both in dry and wet GDL, while the water transport accompanied heat conduction and convection are also crucial in wet GDL. However, the effects of water transport on the electrical conduction can be ignored due to the significant differences of the electrical conductivities between water and solid fibrous layers. Besides, the interactions between vapor condensation and heat transfer are explored, it is shown that the temperature of the fibers under the rib is lower than that of other fibers, leading to a higher condensate water saturation and a lager droplet size at the corresponding positions. The results presented here are significantly helpful to deepen our knowledge on the interactions between heat transfer and water transport, and guide the heat and water management in the PEMFC.